Bark beetles of coniferous trees in Botanical Garden of V. N. Karazin Kharkiv National University - Zinchenko, O. V.; Kukina, O. M.; Skrylnyk, Yu. Ye. (Forestry and Forest Melioration, 2019)
Introduction Bark beetles are among the main causes of Norway spruce Picea abies (Karst.) decline in many regions. Particularly in Ukrainian Carpathians region, Ips typographus L., Ips duplicatus Sahl., Pityogenes chalcographus L., Ірs acuminatus Gyll, Ips amitinus Eichh, Pityophthorus micrographus L., Crypturgus pusillus Gyll., and Hylastes cunicularius Er. havecolonized Norway spruce. Since 2011, the health condition of coniferous trees in the Botanical Garden of V. N. Karazin Kharkiv National University has been deteriorating because of bark beetles' attacks. The aim of our research was to identify the species composition of bark beetles in coniferous tree species in the Botanical Garden of V. N. Karazin Kharkiv National University. Materials and Methods The research was carried out in the Botanical Garden of V. N. Karazin Kharkiv National University (50°01?N, 36°13?E, altitude 140–150 m a.s.l.) during the growing season 2019. We inspected 198 coniferous trees, including 36 species from 7 genera: fir (Abies), spruce (Picea), pine (Pinus), Douglas fir (Pseudotsuga), juniper (Juniperus), larch (Larix), and yew (Taxus). We collected the insects from lower branches, stems and galleries in drying up trees. Then we identified them in laboratory conditions. Results Four species of bark beetles were identified (Ips typographus L., Pityogenes chalcographus L., Crypturgus cinereus Herb., and C. subcribrosus Eg.) on coniferous trees in the territory of the Botanical Garden. Only five species of fir (Abies balsamia, A. cephalonica, А. concolor, A. grandis, and А. violacea.) didn’t have any symptoms of colonization. fraseri and A. nordmanniana were colonized only by Pityogenes chalcographus, A. veitchii – by Crypturgus cinereus. A. arizonica and A. lasiocarpa were colonized by two bark beetles species – Ips typographus and Crypturgus subcribrosus. Picea obovate was colonized by three bark beetle species that is all found species except Ips typographus. obovata 'Glauca' proved to be the most susceptible for bark beetles' attacks, as it was colonized by all four identified bark beetles. No bark beetle colonization was found on P. kochiana and P. nigra. P. banksiana and P. peuce were colonized by Ips typographus, and P. strobus – by Ips typographus, Crypturgus cinereus colonizations. P. Pallasiana trees were colonized only by Pityogenes chalcographus. Larix sp. and Pseudotsuga menziesii 'Glauka' were colonized by Ips typographus and Pityogenes chalcographus. Ips typographus proved to be the most common bark beetles species on inspected trees and was identified on 18 species coniferous trees. Conclusions Four species of bark beetles were identified (Ips typographus L., Pityogenes chalcographus L., Crypturgus cinereus Herb., and C. subcribrosus Eg.) on coniferous trees in the territory of the Botanical Garden. Only five species of the Abies genus had no signs of colonizing with bark beetles, namely: A. balsamia, A. cephalonica, A. concolor, A. grandis, and A. violacea. Picea koraiensis and P. alba were not inhabited by bark beetles, but colonization attempts were found on the stem. P. obovata of the 'Glauca' form was inhabited by all identified bark beetle species. Ips typographus was the most common on the spruce among other bark beetles. Among 198 surveyed trees, 27.3 % had no signs of colonization by bark beetles, 9.9 % had the attempts of colonization, and 63.6 % were inhabited by bark beetles. 1 Table, 17 Refs.